Renewable energy consumption optimization allocation strategy for a regional microgrid based on a shared energy storage mechanism - Ma, Hongde; Zhang, Weiqi; Luo, Ziqing (Frontiers in Energy Research, 2025)
With the continuous maturation of the sharing economy model, the shared energy storage station service model emerges as a promising user-side energy storage application. This article proposes a bilayer optimal configuration method for regional microgrid systems, leveraging shared energy storage station services. First, this article introduces and analyzes the new model’s operation mechanism and profit model (the financial framework that outlines how the shared energy storage station service generates revenue and manages costs to achieve profitability), emphasizing its role in energy sharing governance to enhance economic and operational efficiency within the microgrid system. Second, this service model was applied to a combined cooling, heating, and power regional microgrid system. Aiming at the multiple goals of the lowest operating cost of the energy storage station and the best economic operation of the regional microgrid, a bilayer optimization model was established. The outer model aims to solve the configuration problem of energy storage stations, while the inner model is responsible for optimizing the economic consumption rate (the efficiency with which energy is utilized within the regional microgrids, considering the costs of its generation, storage, and distribution) and the operation of regional microgrids. Based on the Karush–Kuhn–Tucker (KKT) condition of the inner layer optimization model, the inner layer model is transformed into the constraint conditions of the outer layer model, and the Big-M method is adopted to linearize the nonlinear problems in the model. Finally, the rationality and effectiveness of the proposed bilayer optimization model were verified through a case analysis of three typical scenarios. The research results show that after configuring shared energy storage, the operating cost of the regional microgrid system decreases by 15.12%, the new energy consumption rate increases to 97.44%, and the shared energy storage service provider can recover the investment cost within 4.62 years. This indicates that the proposed method for constructing a bilayer optimization configuration can effectively consider the economic consumption of new energy and significantly improve the economic operation of shared energy storage stations and regional microgrids.